Modulating Myogenesis: An Optimized In Vitro Assay to Pharmacologically Influence Primary Myoblast Differentiation. Issue 9 (27th September 2022) - VanGenderen, Cordell A.; Granet, Jules A.; Filippelli, Romina L.; Liu, Yiyang; Chang, Natasha C.
Abstract: The intentional pharmacological manipulation of myogenesis is an important technique for understanding the underlying mechanisms of muscle differentiation and disease etiology. Using the pharmacological agent metformin as an example molecule, we present a systematic approach to examine the impact of pharmacological agents on the myogenic program. This consists of optimizing the in vitro differentiation of primary myoblast cells followed by the generation of a dose‐response curve for a respective pharmaceutical. To assess myogenic differentiation, we utilized three approaches (incorporating both transcriptional and protein techniques) to assess the effects of biologically active agents on the in vitro differentiation of primary myogenic progenitors. First, the immunofluorescent visualization of myosin heavy chain (MYHC), which is expressed in differentiated myofibers, is used to obtain the fusion index, a quantitative read‐out of differentiation efficiency. Second, quantitative reverse transcription PCR (RT‐qPCR) reveals the expression of myogenic factors ( Pax7, Myf5, Myod, Myog, Myh2 ) at the transcript level. Third, western blotting is used to assess the protein expression levels of the myogenic markers (PAX7, MYF5, MYOD, MYOG, and MYHC). By monitoring the expression of these various myogenic factors during the differentiation process, the relative cellular state and differentiation status between samples can be determined. Combined, these approaches enable the successful assessment of the impact of pharmacological agents on myogenic differentiation. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Immunofluorescence assay for qualitative and quantitative assessment of pharmacological agents on in vitro myogenic differentiation Support Protocol 1 : Evaluating myogenic gene expression by RT‐qPCR Support Protocol 2 : Evaluating myogenic protein expression by western blot